UNSUR ESTETIKA PADA KARAKTER DAN CERITA ANIMASI ADIT SOPO JARWO - Saputra, Dewa Gede Wirya Nanda; Dwipayana, I Kadek Angga; Alrizkian, Firzi Raihan; Alfahkri, Armansyah Rizki; Putra, Gede Lingga Ananta Kusuma (Anima Rupa, 2023)
Adit Sopo Jarwo is one of the most popular animated series in Indonesia. In this series, there are many aesthetic elements that make it interesting and entertaining. These elements include character design, animation, backgrounds, music, and narration. The character designs in Adit Sopo Jarwo are very unique and alluring. This article uses two methods in this research, namely literature study and observation. Aesthetics in animation also involves choosing the right colors. Color can be used to create different moods in animated scenes. For example, bright, cheery colors could be used for scenes that are happy and cheery, while dark, muted colors could be used for scenes that are mysterious or scary. The aesthetics of the animated film "Adit Sopo Jarwo" brings the conclusion that this film has an attractive visual quality. The use of 3D animation provides subtle detail and gives life to the characters. The arrangement of bright and cheerful colors creates a fun and kid-friendly atmosphere. In addition, the unique and diverse character designs are also the main attraction of this film.